Why Worry About Climate Change? A Research Agenda - Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2006)
Estimates of the marginal damage costs of carbon dioxide emissions suggest that, although climate change is a problem and some emission reduction is justified, very stringent abatement does not pass the cost-benefit test. However, current estimates of the economic impact of climate change are incomplete. Some of the missing impacts are likely to be positive and others negative, but overall the uncertainty seems to concentrate on the downside risks and current estimates of the damage costs may have a negative bias. The research effort on the economic impacts of climate change is minute, and should be strengthened, with a particular focus on the quantification of uncertainties; estimating missing impacts, interactions between impacts and higher-order effects; the valuation of biodiversity loss; the implications of extreme climate scenarios and violent conflict; and climate change in the very long term.
Keywords: Q54; 330; Climate Change; Impacts; Valuation; Cost-benefit Analysis; Klimaveränderung; Umweltbelastung; Volkswirtschaftlicher Schaden; Kosten-Nutzen-Analyse